Enhancing Subsurface Geological Model Resolution in Challenging Seismic Conditions by Using Model-Based Deterministic Inversion - Mawalid, Abi; Haris, Abdul; Wijanarko, Edy (Scientific Contributions Oil and Gas, 2026)
The limited resolution of 2D seismic data often limits the accuracy of subsurface interpretation. This study explores how deterministic inversion enhances the elastic representation of low-resolution intervals in Field X and contributes to more precise reservoir interpretation. By applying deterministic inversion, this study aims to improve the mapping of lithological variations throughout the interval. Petrophysical data show that the target zone contains porosity values of 11–22%, Gamma Ray readings of 10–120 API, and P-impedance values of 11022–15343. These parameters support well–seismic tying and model calibration. The inversion generates an acoustic impedance model that closely aligns with the log trends and shows a coherence error of only 6.23% within the target interval. Domains with increased permeability and reduced GR readings appear as subtle impedance irregularities, whereas more consolidated phases show higher impedance. The resulting impedance response captures geologically meaningful mid-range lithological variations, although limitations in seismic resolution still reduce the precision of stratigraphic delineation. Overall, the findings demonstrate that careful calibration with petrophysical datasets provides a consistent and quantifiable impedance framework, even in areas with limited seismic fidelity, thereby supporting more reliable reservoir interpretation.